Review on the research of the global emergency communication spectrum - Xiaoyong LIU; Xixi FAN; Lin ZHU; Yuanxin YAO (Dianxin kexue)
The construction of an emergency private network is the necessity of unified command and dispatch communications in rescue of disasters, emergency response, and major activity safeguard.It is an important communication means of public safety protection.With the rapid development of radio technology, the traditional narrowband emergency communication system is difficult to meet the needs of multimedia data, interconnection, anti-interference and other needs under the new situation.Digitization, broadband and ubiquity have become the inevitable trend of the development of emergency private networks.First of all, the technical system and development trend of emergency communication were summarized, the global emergency communication research framework were introduced, the frequency planning and current use status of the emergency private network in the United States, Europe, Asia-Pacific and other countries and regions were analyzed.Finally, combine with the current frequency planning, suggestions for the construction of China’s emergency private network from the aspects of technology trends, industrial development, frequency band selection, and construction mode were presented.